Immobilization of Ntn hydrolases on APTES fuctionalized SBA-15 - Shah, Pallavi; Sridevi, N.; Prabhune, Asmita; Ramaswamy, Veda (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
APTES Functionalized mesoporous silica SBA-15 molecular sieves have been prepared and used for immobilization of Penicillin G acylase. Physico chemical characterization was done by nitrogen adsorption, powder XRD and TEM methods to understand the nature of immobilized PGA enzyme. XRD data indicate a good mesoscopic order. The characteristic hexagonal features of SBA-15 were maintained in PGA immobilized SBA-15 samples. Incorporation of PGA does not affect the original pore structure of the parent SBA-15. The adsorption of PGA on SBA-15 from buffered solutions with a pH value, 7.8 has been studied as a model protein adsorption system. The maximum activity of the immobilized enzyme was observed at pH 7.8, slightly below the isoelectric point of the enzyme. The loading capacity of immobilized PGA is 34 mg protein per 0.5 g of SBA-15. The stability of Penicillin G acylase was enhanced by the physical entrapment in SBA-15.